2019
DOI: 10.1073/pnas.1900523116
|View full text |Cite
|
Sign up to set email alerts
|

A spatially dynamic network underlies the generation of inspiratory behaviors

Abstract: The ability of neuronal networks to reconfigure is a key property underlying behavioral flexibility. Networks with recurrent topology are particularly prone to reconfiguration through changes in synaptic and intrinsic properties. Here, we explore spatial reconfiguration in the reticular networks of the medulla that generate breathing. Combined results from in vitro and in vivo approaches demonstrate that the network architecture underlying generation of the inspiratory phase of breathing is not static but can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 92 publications
6
42
0
Order By: Relevance
“…However, the refractory period is not absolute as it can be overcome 519 if the stimulus is of sufficient strength (Vann et al, 2018). Using a stimulus procedure 520 consistent with previous reports (Baertsch et al, 2018, Baertsch et al, 2019 and Del Negro, 2015), we found that SP does not change the duration of the refractory 522 period. This finding is consistent with our demonstration that excitatory neurons do not 523…”
Section: In Glutamatergic 513supporting
confidence: 75%
See 1 more Smart Citation
“…However, the refractory period is not absolute as it can be overcome 519 if the stimulus is of sufficient strength (Vann et al, 2018). Using a stimulus procedure 520 consistent with previous reports (Baertsch et al, 2018, Baertsch et al, 2019 and Del Negro, 2015), we found that SP does not change the duration of the refractory 522 period. This finding is consistent with our demonstration that excitatory neurons do not 523…”
Section: In Glutamatergic 513supporting
confidence: 75%
“…493 Furthermore, recent evidence suggests that inspiratory neurons located rostral to 494 the preBӧtC also contribute to the dynamic regulation of breathing frequency (Baertsch 495 et al, 2019). However, under normal conditions, inhibition restrains the rhythm 496 generating ability of these rostral neurons, as recruitment of these neurons is 497 associated with increased excitation during inspiratory bursts, a prolonged refractory 498 phase, and consequently a decreased respiratory frequency (Baertsch et al, 2019). 499…”
Section: Discussion: 431mentioning
confidence: 99%
“…3 k,l), we speculate that a decrease in the synaptic efficacy following network synchronization, e.g., due to increased neuronal conductance, contributes to burstlet/burst termination 48 . While not essential to rhythmogenesis, the inhibition originating in the preBötC does regulate the duration of I-bursts, and modulate breathing pattern 5,7,8,25,49 .…”
Section: Main Textmentioning
confidence: 99%
“…2g1-i, S2d1-e). Given that the excitation-inhibition balance in a network is a critical determinant of its output 24 , including for breathing 5,8,25,26 , we hypothesize that that net impact of increased [K + ] ACSF is to shift the excitation-inhibition balance towards higher excitation, which favors preBötC synchronization. To test this hypothesis, we disinhibited the network by antagonizing gamma-aminobutyric acid type A (GABA A ) or glycinergic receptors.…”
Section: Main Textmentioning
confidence: 99%
“…It has recently been proposed that the post-inspiratory complex (PiCo) in the brainstem functions as a network oscillator to coordinate this phase of breathing with other central respiratory oscillators, and to produce state-dependent modulations as required for metabolic demands or precision motor acts (Anderson, Garcia, Baertsch, Pollak, Bloom, Wei, Rai, & Ramirez, 2016;Baertsch, Severs, Anderson, & Ramirez, 2019). This is different and potentially adjunctive to laryngeal adduction, which has been classically used to define E1 (Bartlett Jr, 1989;Bartlett Jr, Remmers, & Gautier, 1973;Harding, 1984).…”
Section: Yield: a Novel Description Of Diaphragm Activity During Earlmentioning
confidence: 99%